Factors associated with postoperative hypocalcemia following thyroidectomy in childhood. Issue 8 (7th February 2022) - Spinelli, Claudio; Ghionzoli, Marco; Bertocchini, Alessia; Sanna, Beatrice; Plessi, Carlotta; Strambi, Silvia; De Napoli, Luigi; Frustaci, Gianluca; Materazzi, Gabriele; Antonelli, Alessandro; Morganti, Riccardo; Gennari, Fabrizio; et al.
Abstract: Background: Postoperative hypocalcemia is a frequent complication after thyroidectomy. Hypoparathyroidism may develop as transient (TtHP), with normalization within six months from surgery, or permanent (PtHP) if the patient requires replacement therapy. We analyzed factors associated with the development of postoperative hypoparathyroidism and in detail PtHP following thyroid surgery in a pediatric population. Procedure: A retrospective multicenter study analyzing 326 patients was carried out. We recorded gender, age, tumor size, thyroiditis, extrathyroidal extension, lymph node dissection (central/lateral compartment, unilateral/bilateral), parathyroid autotransplantation, and histology. Additionally, calcium levels were acquired postoperatively. Results: We analyzed pediatric patients ≤18 years who underwent thyroidectomy clustered into age groups (≤15 or > 15). Patients' mean follow‐up was 5.8 years (1‐11 years). Postoperative hypoparathyroidism occurred in 36 (11.0%): 20 cases (6.13%) developed PtHP. Postoperative hypoparathyroidism was more frequent in younger patients ( P = 0.014), in larger tumors ( P < 0.001), in case of extrathyroidal extension ( P = 0.037), and in central compartment ( P = 0.020) and bilateral lymph node dissection ( P = 0.030). PtHP was more frequent in older patients ( P = 0.014), in case of thyroiditis ( P < 0.001), and extrathyroidal extension ( P < 0.001). Concerning the first postoperative calcium level measurement, in the postoperative hypoparathyroidism group, we registered a 8.17 mg/dL value with 14% pre/postoperative decrease (ΔCa ), whereas in PtHP patient group calcium level was 7.91 mg/dL with 16.7% ΔCa . Conclusions: The risk of postoperative hypoparathyroidism is related to younger age, tumor size, central compartment and bilateral lymph node dissection, extrathyroidal extension, and decrease in postoperative calcium levels. The risk of PtHP is related to older age, thyroiditis, extrathyroidal extension, and decrease in postoperative calcium levels.